Mft1, identified from a genome-wide screen of the yeast haploid mutants, mediates cell cycle arrest to counteract quinoxaline-induced toxicity - Sulaiman, Abdallah Alhaj; Al-Ansari, Dana E.; Ali, Reem; Aouida, Mustapha; Ramotar, Dindial (Frontiers in Genetics, 2024)
Quinoxaline is a heterocyclic compound with a two-membered ring structure that undergoes redox cycling to produce toxic free radicals. It has antiviral, antibacterial, antifungal, and antitumor activities. However, the biological functions that are involved in mounting a response against the toxic effects of quinoxaline have not been investigated. Herein, we performed a genome-wide screen using the yeast haploid mutant collection and reported the identification of 12 mutants that displayed varying sensitivity towards quinoxaline. No mutant was recovered that showed resistance to quinoxaline. The quinoxaline-sensitive mutants were deleted for genes that encode cell cycle function, as well as genes that belong to other physiological pathways such as the vacuolar detoxification process. Three of the highly sensitive gene-deletion mutants lack the DDC1, DUN1, and MFT1 genes. While Ddc1 and Dun1 are known to perform roles in the cell cycle arrest pathway, the role of Mft1 remains unclear. We show that the mft1Δ mutant is as sensitive to quinoxaline as the ddc1Δ mutant. However, the double mutant ddc1Δ mft1Δ lacking the DDC1 and MFT1 genes, is extremely sensitive to quinoxaline, as compared to the ddc1Δ and mft1Δ single mutants. We conclude that Mft1 performs a unique function independent of Ddc1 in the cell cycle arrest pathway in response to quinoxaline exposure. This is the first demonstration that quinoxaline exerts its toxic effect likely by inducing oxidative DNA damage causing cell cycle arrest. We suggest that clinical applications of quinoxaline and its derivatives should entail targeting cancer cells with defective cell cycle arrest.